Modified talcum powder as well as preparation method and application thereof
Through the hydrogen bonding of modified talc powder and polysaccharides and the accumulation void design of modified calcium powder, the problem of difficult to rapidly degrade existing reflective film materials is solved, and a faster degradation and a more environmentally friendly production process is achieved.
Patent Information
- Application Number
- CN202510001892.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
Existing agricultural reflective film materials are difficult to degrade quickly after use, resulting in environmental pollution and safety risks, and there are few researches on biodegradable reflective films.
By reacting talc powder with organic carboxylic acid to form carboxylic acid modified talc powder and connecting it with polysaccharides through hydrogen bonds, modifying calcium powder forms accumulating voids in the reflective film, promoting the reproduction of bacteria and fungi and accelerating the degradation of the reflective film.
It realizes rapid degradation of reflective film, faster degradation speed, simple production operation, more environmentally friendly, and reduces environmental pollution and safety risks.
Smart Images

Figure BDA0005225538650000091
Abstract
Description
Technical Field
[0001] The invention relates to the field of biodegradable materials, in particular to modified talcum powder, a preparation method thereof and application thereof. Background Art
[0002] Agricultural reflective film is mainly used for the brightening of grapes, apples, peaches and other fruits after picking, aiming to improve the coloring of the fruit. The coloring period of fruit trees is relatively short, and the service life of agricultural reflective film is usually limited to about one month. The mainstream agricultural reflective film materials on the current market are mostly PET. After use, such materials face problems such as difficulty in recycling, easy light pollution, and possible fire caused by wind blowing to power lines. Therefore, it is necessary to develop a reflective film material that can be quickly degraded after use, has little environmental pollution and low risk, so as to fundamentally solve the hazards caused by existing products.
[0003] Currently, there is little research on biodegradable reflective film for fruit trees. CN114771071A discloses a three-layer degradable composite film and its preparation method, but the film is thick and expensive, and cannot be quickly degraded after use. CN113584434A discloses a double-layer degradable aluminum-plated film and its preparation method, but the preparation of its reinforcing fiber layer is complicated and affects the glossiness.
[0004] Therefore, how to provide a biodegradable and rapidly degradable reflective film for fruit trees has a very positive significance. Summary of the invention
[0005] In view of the above problems existing in the prior art, the purpose of the present invention is to provide a modified talcum powder, a preparation method thereof and an application thereof, which utilizes hydrogen bonds to connect polysaccharides on the surface of the talcum powder, and utilizes the accumulation gaps formed by the modified calcium powder in the reflective film to make it easier for bacteria and fungi to enter the interior of the reflective film and reproduce rapidly, thereby accelerating the degradation of the reflective film.
[0006] Another object of the present invention is to provide an application of the modified talcum powder prepared by the above method, which can be used to prepare a degradable reflective film, and the prepared degradable reflective film has a faster degradation rate.
[0007] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is as follows:
[0008] In a first aspect, the present invention provides a method for preparing modified talcum powder, comprising the following steps:
[0009] The talc powder is mixed with an organic carboxylic acid and reacted under the action of a catalyst to obtain carboxylic acid-modified talc powder.
[0010] In the present invention, the particle size of the talc powder is 3000-5000 mesh.
[0011] In the present invention, the organic carboxylic acid has a general formula of R-COOH, wherein R represents an alkyl group or an aromatic group, preferably a C1-C5 alkyl group.
[0012] Preferably, the organic carboxylic acid is selected from one or more of formic acid and acetic acid.
[0013] In the present invention, the mass ratio of the talc to the organic carboxylic acid is 1:5-1:20.
[0014] In the present invention, the catalyst is an acid, and the amount used is 2-8% of the mass of the organic carboxylic acid.
[0015] Preferably, the catalyst is selected from one or more of sulfuric acid and phosphoric acid, preferably concentrated sulfuric acid with a concentration of 80 wt % or more or concentrated phosphoric acid with a concentration of 70 wt % or more.
[0016] In the present invention, the reaction is carried out under reflux conditions at a temperature of 100-170° C. for 6-12 hours.
[0017] In the present invention, the preparation of modified talc powder also includes post-processing steps such as washing and drying.
[0018] In a second aspect, the present invention provides modified talc prepared by the above preparation method.
[0019] In a third aspect, the present invention provides the use of modified talc prepared by the preparation method of the present invention in a degradable reflective film, which can increase the degradation rate of the degradable reflective film.
[0020] A degradable reflective film, comprising a bright layer and a disintegrating layer, wherein the bright layer comprises the following components in parts by weight:
[0021] PBAT 96-98 copies,
[0022] Degradation aid 0.5-1.5 parts,
[0023] Nucleating agent 0-3 parts;
[0024] The disintegrating layer comprises the following components in parts by weight:
[0025] PBAT 50-80 parts;
[0026] 20-40 parts of carboxylic acid modified talc;
[0027] Polysaccharide 0.1-10 parts;
[0028] 0.5-1.5 parts of degradation aid;
[0029] Opening agent 0.1-0.5 parts
[0030] The degradation aid of the present invention is one or more of iron stearate, titanium dioxide, manganese stearate and cerium stearate.
[0031] The modified talc powder is the modified talc powder prepared by the preparation method described in the present invention.
[0032] Preferably, the amount of polysaccharide added is 0.2-5 parts by mass.
[0033] In the present invention, the polysaccharide is one or more of cellulose, starch, glycogen, and chitosan, and the polysaccharide can form hydrogen bonds with modified talc.
[0034] The opening agent of the present invention is one or more of oleamide, erucic acid amide and ethylene bisstearamide.
[0035] The nucleating agent of the present invention is one or more of silicon dioxide, montmorillonite, diphenyl dihydrazide adipic acid and sodium benzoate.
[0036] Preferably, an aluminum layer is provided above the bright layer.
[0037] Preferably, the thickness of the disintegration layer is 11-15 μm, the thickness of the bright layer is 4-5 μm, and the thickness of the aluminum layer is 20-40 nm.
[0038] In a fourth aspect, the present invention provides a method for preparing a biodegradable reflective film, comprising the following steps:
[0039] S1: Preparation of degradation modified materials;
[0040] S11: PBAT, carboxylic acid modified talc, polysaccharide, degradation aid, and opening agent are melt-mixed and pelletized by a twin-screw extruder to prepare a disintegrating layer modified material;
[0041] S12: melt-mixing PBAT, a degradation aid, and a nucleating agent through a twin-screw extruder, and pelletizing to prepare a bright layer modified material;
[0042] S2: Preparation of biodegradable reflective film;
[0043] S21: The modified materials prepared in S11 and S12 are used in a double-layer film blowing machine to prepare a degradable base film, which comprises a bright layer and a disintegration layer from top to bottom;
[0044] S22: coating an aluminum layer on the degradable base film obtained in S21 to obtain a biodegradable reflective film.
[0045] In step S21 of the present invention, the degradable base film is evenly rolled up after being pulled and trimmed, with the bright layer facing upward; preferably, the width of the degradable base film is 80-250 cm.
[0046] In step S21 of the present invention, the degradable base film can be prepared into a degradation layer of corresponding thickness by controlling the extrusion speed of each extruder. The speed can be conventionally selected by those skilled in the art and will not be elaborated here.
[0047] Preferably, the carboxylic acid-modified talc is first fully mixed with the polysaccharide and then added to the extruder.
[0048] Talc reacts with R-COOH to form ester groups on the surface, which combine with polysaccharides capable of forming hydrogen bonds in the molten state due to hydrogen bonding, so that the surface of talc is grafted and coated with polysaccharides, thereby providing a living place for bacteria and fungi.
[0049] Compared with the prior art, this application has the following beneficial effects:
[0050] By reacting talcum powder with R-COOH to form esters on the surface, hydrogen bonds are used to connect and wrap polysaccharides on the surface, and the accumulation gaps formed by modified talcum powder in the reflective film make it easier for bacteria and fungi to enter the reflective film and reproduce rapidly, thereby accelerating the degradation of the reflective film. The degradable reflective film prepared by the present application has a faster degradation speed, simple production operation, and is more environmentally friendly, and is worthy of promotion. DETAILED DESCRIPTION
[0051] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention is further described in detail below through specific implementation methods, but this should not be understood as the scope of the present invention being limited to the following examples. Without departing from the above-mentioned inventive concept of the present invention, various substitutions or changes made according to common technical knowledge and customary means in the art should be included in the scope of the present invention.
[0052] The raw materials used in the embodiments of the present invention are shown in Table 1 below.
[0053] Table 1 Raw materials and sources
[0054] product Brand factory PBAT resin T16 Whchem Concentrated sulfuric acid (98wt%) / Innochem Glycogen Glycogen Innochem Acetic acid Hac Innochem starch TPS Innochem talcum powder Talc Hisun 101 Iron stearate FeSt3 Innochem Sodium Benzoate / Innochem Erucamide / Innochem
[0055] The "parts" mentioned in the specific implementation methods of this application are all "parts by mass".
[0056] Example 1
[0057] (1) Prepare modified talcum powder by:
[0058] Talc and acetic acid were added to a round-bottom flask at a mass ratio of 1:5, and concentrated sulfuric acid (concentration 98wt%) with a mass percentage of 2wt% of the mass of acetic acid was added dropwise, and the mixture was heated to 120°C in an oil bath for 12h. After the reaction was completed, the excess acetic acid was removed by a rotary evaporator, and then washed with a 5wt% Na2CO3 aqueous solution and dried to obtain modified talc.
[0059] (2) 64.8 parts of PBAT, 30 parts of modified talc, 4 parts of glycogen, 1 part of iron stearate, and 0.2 parts of erucamide were melt-mixed and pelletized by a twin-screw extruder to prepare a disintegrating layer modified material. The extrusion temperature was set to 150-180° C. and the screw speed was set to 200-400 rpm.
[0060] (3) 96 parts of PBAT, 1 part of iron stearate, and 3 parts of sodium benzoate were melt-mixed and pelletized by a twin-screw extruder to prepare a bright layer modified material. The extrusion temperature was set to 150-180° C. and the screw speed was set to 400-600 rpm.
[0061] (4) The modified materials prepared by (2) and (3) were used to prepare a degradable base film by a double-layer film blowing machine. The film blowing temperature was set at 150-180°C. The film was composed of a glossy layer and a disintegration layer from top to bottom. The thickness of the disintegration layer in the degradable base film was 11 μm and the thickness of the glossy layer was 4 μm.
[0062] (5) The biodegradable base film obtained in (4) is subjected to vacuum evaporation of aluminum on the bright surface by a coating machine to prepare a biodegradable reflective film, wherein the thickness of the aluminum layer is 30 nm.
[0063] Example 2
[0064] (1) Prepare modified talcum powder by:
[0065] Talc and formic acid were added to a round-bottom flask at a mass ratio of 1:10, and concentrated sulfuric acid (concentration 98wt%) with a mass percentage of 6wt% of formic acid was added dropwise, and heated to 120°C in an oil bath for 12h. After the reaction was completed, excess formic acid was removed by rotary evaporator, and then washed with 5wt% Na2CO3 aqueous solution and dried to obtain modified talc.
[0066] (2) 68.3 parts of PBAT, 30 parts of modified talc, 0.5 parts of glycogen, 1 part of iron stearate, and 0.2 parts of erucic acid amide were melt-mixed and pelletized by a twin-screw extruder to prepare a disintegrating layer modified material. The extrusion temperature was set to 150-180° C. and the screw speed was set to 200-400 rpm.
[0067] (3) 96 parts of PBAT, 1 part of iron stearate, and 3 parts of sodium benzoate were melt-mixed and pelletized by a twin-screw extruder to prepare a bright layer modified material. The extrusion temperature was set to 150-180° C. and the screw speed was set to 400-600 rpm.
[0068] (4) The modified materials prepared by (2) and (3) were used to prepare a degradable base film by a double-layer film blowing machine. The film blowing temperature was set at 150-180°C. The film was composed of a glossy layer and a disintegration layer from top to bottom. The thickness of the disintegration layer in the degradable base film was 14 μm and the thickness of the glossy layer was 5 μm.
[0069] (5) The biodegradable base film obtained in (4) is subjected to vacuum evaporation of aluminum on the bright surface by a coating machine to prepare a biodegradable reflective film, wherein the thickness of the aluminum layer is 35 nm.
[0070] Example 3
[0071] (1) Prepare modified talcum powder by:
[0072] Talc and acetic acid were added to a round-bottom flask at a mass ratio of 1:15, and concentrated sulfuric acid (concentration 98wt%) with a mass percentage of 2wt% of the mass of acetic acid was added dropwise, and the mixture was heated to 120°C in an oil bath for 12h. After the reaction was completed, the excess acetic acid was removed by a rotary evaporator, and then washed with a 5wt% Na2CO3 aqueous solution and dried to obtain modified talc.
[0073] (2) 67.8 parts of PBAT, 30 parts of modified talc, 1 part of starch, 1 part of iron stearate, and 0.2 parts of erucamide were melt-mixed and pelletized by a twin-screw extruder to prepare a disintegrating layer modified material. The extrusion temperature was set to 150-180° C. and the screw speed was set to 200-400 rpm.
[0074] (3) 96 parts of PBAT, 1 part of iron stearate, and 3 parts of sodium benzoate were melt-mixed and pelletized by a twin-screw extruder to prepare a bright layer modified material. The extrusion temperature was set to 150-180° C. and the screw speed was set to 400-600 rpm.
[0075] (4) The modified materials prepared by (2) and (3) were used to prepare a degradable base film by a double-layer film blowing machine. The film blowing temperature was set at 150-180°C. The film was composed of a glossy layer and a disintegration layer from top to bottom. The thickness of the disintegration layer in the degradable base film was 14 μm and the thickness of the glossy layer was 5 μm.
[0076] (5) The biodegradable base film obtained in (4) is subjected to vacuum evaporation of aluminum on the bright surface by a coating machine to prepare a biodegradable reflective film, wherein the thickness of the aluminum layer is 30 nm.
[0077] Example 4
[0078] (1) Prepare modified talcum powder by:
[0079] Talc and acetic acid were added to a round-bottom flask at a mass ratio of 1:15, and concentrated sulfuric acid (concentration 98wt%) with a mass percentage of 2wt% of the mass of acetic acid was added dropwise, and the mixture was heated to 120°C in an oil bath for 12h. After the reaction was completed, the excess acetic acid was removed by a rotary evaporator, and then washed with a 5wt% Na2CO3 aqueous solution and dried to obtain modified talc.
[0080] (2) 72.8 parts of PBAT, 25 parts of modified talc, 1 part of starch, 1 part of iron stearate, and 0.2 parts of erucamide were melt-mixed and pelletized by a twin-screw extruder to prepare a disintegrating layer modified material. The extrusion temperature was set to 150-180° C. and the screw speed was set to 200-400 rpm.
[0081] (3) 96 parts of PBAT, 1 part of iron stearate, and 3 parts of sodium benzoate were melt-mixed and pelletized by a twin-screw extruder to prepare a bright layer modified material. The extrusion temperature was set to 150-180° C. and the screw speed was set to 400-600 rpm.
[0082] (4) The modified materials prepared by (2) and (3) were used to prepare a degradable base film by a double-layer film blowing machine. The film blowing temperature was set at 150-180°C. The film was composed of a glossy layer and a disintegration layer from top to bottom. The thickness of the disintegration layer in the degradable base film was 14 μm and the thickness of the glossy layer was 5 μm.
[0083] (5) The biodegradable base film obtained in (4) is subjected to vacuum evaporation of aluminum on the bright surface by a coating machine to prepare a biodegradable reflective film, wherein the thickness of the aluminum layer is 30 nm.
[0084] Example 5
[0085] (1) Prepare modified talcum powder by:
[0086] Talc and acetic acid were added to a round-bottom flask at a mass ratio of 1:15, and concentrated sulfuric acid (concentration 98wt%) with a mass percentage of 2wt% of the mass of acetic acid was added dropwise, and the mixture was heated to 120°C in an oil bath for 12h. After the reaction was completed, the excess acetic acid was removed by a rotary evaporator, and then washed with a 5wt% Na2CO3 aqueous solution and dried to obtain modified talc.
[0087] (2) 63.3 parts of PBAT, 35 parts of modified talc, 0.5 parts of starch, 1 part of iron stearate, and 0.2 parts of erucic acid amide were melt-mixed and pelletized by a twin-screw extruder to prepare a disintegrating layer modified material. The extrusion temperature was set to 150-180° C. and the screw speed was set to 200-400 rpm.
[0088] (3) 98 parts of PBAT, 1 part of iron stearate, and 2 parts of sodium benzoate were melt-mixed and pelletized by a twin-screw extruder to prepare a bright layer modified material. The extrusion temperature was set to 150-180° C. and the screw speed was set to 400-600 rpm.
[0089] (4) The modified materials prepared by (2) and (3) were used to prepare a degradable base film by a double-layer film blowing machine. The film blowing temperature was set at 150-180°C. The film was composed of a glossy layer and a disintegration layer from top to bottom. The thickness of the disintegration layer in the degradable base film was 14 μm and the thickness of the glossy layer was 5 μm.
[0090] (5) The biodegradable base film obtained in (4) is subjected to vacuum evaporation of aluminum on the bright surface by a coating machine to prepare a biodegradable reflective film, wherein the thickness of the aluminum layer is 20-40 nm.
[0091] Example 6
[0092] (1) Prepare modified talcum powder by:
[0093] Talc and acetic acid were added to a round-bottom flask at a mass ratio of 1:10, and concentrated sulfuric acid (concentration 98wt%) with a mass percentage of 2wt% of the mass of acetic acid was added dropwise, and the mixture was heated to 120°C in an oil bath for 12h. After the reaction was completed, the excess acetic acid was removed by a rotary evaporator, and then washed with a 5wt% Na2CO3 aqueous solution and dried to obtain modified talc.
[0094] (2) 66.8 parts of PBAT, 30 parts of modified talc, 2 parts of starch, 1 part of iron stearate, and 0.2 parts of erucamide were melt-mixed and pelletized by a twin-screw extruder to prepare a disintegrating layer modified material. The extrusion temperature was set to 150-180° C. and the screw speed was set to 200-400 rpm.
[0095] (3) 96 parts of PBAT, 1 part of iron stearate, and 3 parts of sodium benzoate were melt-mixed and pelletized by a twin-screw extruder to prepare a bright layer modified material. The extrusion temperature was set to 150-180° C. and the screw speed was set to 400-600 rpm.
[0096] (4) The modified materials prepared by (2) and (3) were used to prepare a degradable base film by a double-layer film blowing machine. The film blowing temperature was set at 150-180°C. The film was composed of a glossy layer and a disintegration layer from top to bottom. The thickness of the disintegration layer in the degradable base film was 12 μm and the thickness of the glossy layer was 5 μm.
[0097] (5) The biodegradable base film obtained in (4) is subjected to vacuum evaporation of aluminum on the bright surface by a coating machine to prepare a biodegradable reflective film, wherein the thickness of the aluminum layer is 30 nm.
[0098] Comparative Example 1
[0099] (1) 64.8 parts of PBAT, 4 parts of glycogen, 30 parts of talc, 1 part of iron stearate, and 0.2 parts of erucic acid amide were melt-mixed and pelletized by a twin-screw extruder to prepare a disintegrating layer modified material. The extrusion temperature was set to 150-180° C. and the screw speed was set to 200-400 rpm.
[0100] (2) 96 parts of PBAT, 1 part of iron stearate, and 3 parts of sodium benzoate were melt-mixed and pelletized by a twin-screw extruder to prepare a bright layer modified material. The extrusion temperature was set to 150-180° C. and the screw speed was set to 400-600 rpm.
[0101] (3) The modified materials prepared by (1) and (2) were used to prepare a degradable base film through a double-layer film blowing machine. The film blowing temperature was set at 150-180°C. The film was composed of a glossy layer and a disintegration layer from top to bottom. The thickness of the disintegration layer in the degradable base film was 11 μm and the thickness of the glossy layer was 4 μm.
[0102] (4) The biodegradable base film obtained in (3) is subjected to vacuum evaporation of aluminum on the bright surface by a coating machine to prepare a biodegradable reflective film, wherein the thickness of the aluminum layer is 30 nm.
[0103] Comparative Example 2
[0104] (1) 78.8 parts of PBAT, 20 parts of talc, 1 part of iron stearate, and 0.2 parts of erucamide were melt-mixed and pelletized by a twin-screw extruder to prepare a disintegrating layer modified material. The extrusion temperature was set at 150-180° C. and the screw speed was set at 200-400 rpm.
[0105] (2) 96 parts of PBAT, 1 part of iron stearate, and 3 parts of sodium benzoate were melt-mixed and pelletized by a twin-screw extruder to prepare a bright layer modified material. The extrusion temperature was set to 150-180° C. and the screw speed was set to 400-600 rpm.
[0106] (3) The modified materials prepared by (1) and (2) were used to prepare a degradable base film by a double-layer film blowing machine. The film blowing temperature was set at 150-180°C. The film was composed of a glossy layer and a disintegration layer from top to bottom. The thickness of the disintegration layer in the degradable base film was 14 μm and the thickness of the glossy layer was 5 μm.
[0107] (4) The biodegradable base film obtained in (3) is subjected to vacuum evaporation of aluminum on the bright surface by a coating machine to prepare a biodegradable reflective film, wherein the thickness of the aluminum layer is 30 nm.
[0108] Performance Testing:
[0109] The PET aluminum-coated reflective film for fruit trees purchased in the market has an average thickness of 30μm and a film width of 150cm.
[0110] The mechanical properties of the aluminum-plated film were tested according to GB / T1040.3-2006. The glossiness of the aluminum-plated film was tested using a gloss meter.
[0111] Apple trees were selected as the experimental site. The reflective film was laid for 30 days to compare the fruit coloring effects of different aluminum-coated films. After the fruit was colored, the degradation of the base film layer of the composite film was observed.
[0112] The data obtained from the above test are shown in Table 2.
[0113] Table 2 Performance data
[0114]
[0115] The degradation behavior of the film is relatively complex and is often affected by factors such as solar radiation, temperature, humidity, microbial community, and usage conditions. Based on the coloring and degradation results of different reflective films, there is no difference in the coloring effect of biodegradable composite film and PET aluminum-coated reflective film on apples, but by adjusting the components in the degradable base film, the degradation time of the composite film can be regulated, so as to meet the reflective coloring time of apple trees and other fruit trees, and achieve a rapid degradation effect after use.
[0116] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed in the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for preparing modified talcum powder, characterized in that: The following steps are involved: The talc powder is mixed with an organic carboxylic acid and reacted under the action of a catalyst to obtain carboxylic acid-modified talc powder.
2. The preparation method according to claim 1, characterized in that: The particle size of the talcum powder is 3000-5000 mesh; Preferably, the organic carboxylic acid has the general formula R-COOH, wherein R represents an alkyl group or an aromatic group, preferably a C1-C5 alkyl group; Preferably, the organic carboxylic acid is selected from one or more of formic acid and acetic acid; Preferably, the mass ratio of the talc to the organic carboxylic acid is 1:5-1:
20.
3. The preparation method according to claim 1 or 2, characterized in that: The catalyst is an acid, and the amount used is 2-8% of the mass of the organic carboxylic acid; Preferably, the catalyst is selected from one or more of sulfuric acid and phosphoric acid, preferably concentrated sulfuric acid with a concentration of 80 wt% or more or concentrated phosphoric acid with a concentration of 70 wt% or more; Preferably, the reaction temperature is 100-170°C and the reaction time is 6-12h.
4. The modified talc powder prepared according to the preparation method according to any one of claims 1 to 3.
5. Use of the modified talc powder prepared by the preparation method according to any one of claims 1 to 3 in a degradable reflective film.
6. A degradable reflective film, characterized in that: The degradable reflective film comprises a bright layer and a disintegrating layer, wherein the bright layer comprises the following components in parts by weight: PBAT 96-98 copies, Degradation aid 0.5-1.5 parts, Nucleating agent 0-3 parts; The disintegrating layer comprises the following components in parts by weight: PBAT 50-80 parts; 20-40 parts of carboxylic acid-modified talc prepared by the preparation method according to any one of claims 1 to 3; Polysaccharide 0.1-10 parts; 0.5-1.5 parts of degradation aid; 0.1-0.5 parts of opening agent.
7. The degradable reflective film according to claim 6, characterized in that: The degradation aid is one or more of iron stearate, titanium dioxide, manganese stearate and cerium stearate; Preferably, the polysaccharide is one or more of cellulose, starch, glycogen, and chitosan; preferably, the amount of the polysaccharide added is 0.2-5 parts by weight; Preferably, the opening agent is one or more of oleamide, erucamide and ethylene bisstearamide; Preferably, the nucleating agent is one or more of silicon dioxide, montmorillonite, diphenyl dihydrazide adipic acid and sodium benzoate.
8. The degradable reflective film according to claim 7, characterized in that: An aluminum layer is provided above the bright layer; Preferably, the thickness of the disintegration layer is 11-15 μm, the thickness of the bright layer is 4-5 μm, and the thickness of the aluminum layer is 20-40 nm.
9. A method for preparing the biodegradable reflective film according to any one of claims 6 to 8, comprising the following steps: S1: Preparation of degradation modified materials; S11: PBAT, carboxylic acid modified talc, polysaccharide, degradation aid, and opening agent are melt-mixed and pelletized by a twin-screw extruder to prepare a disintegrating layer modified material; S12: melt-mixing PBAT, a degradation aid, and a nucleating agent through a twin-screw extruder, and pelletizing to prepare a bright layer modified material; S2: Preparation of biodegradable reflective film; S21: The modified materials prepared in S11 and S12 are used in a double-layer film blowing machine to prepare a degradable base film, which comprises a bright layer and a disintegration layer from top to bottom; S22: an aluminum layer is applied to the degradable base film obtained in S21 to obtain a biodegradable reflective film.
10. The preparation method according to claim 9, characterized in that: The carboxylic acid-modified talc is firstly fully mixed with the polysaccharide and then added into the extruder; Preferably, in the step S21, the degradable base film is uniformly rolled up after being pulled and trimmed, with the glossy layer facing upward.
Citation Information
Patent Citations
Degradable reinforced aluminium laminated film and preparation method thereof
CN113584434A
Biodegradable composite film for reflecting light of fruit trees and preparation method of biodegradable composite film
CN114771071A